The national development plan 2022-2026: Colombia, world power of life - Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The President of the Republic, Gustavo Petro Urrego, signed Law 2294 on May 19, 2023, which establishes the National Development Plan “Colombia, World Power of Life.” This plan, which will be implemented in the four years 2022-2026, will become the roadmap for economic, social and environmental public policies and government investments.The plan consists of 372 articles and provides for public investments worth 1,154 billion. Half of these resources will come from the General Budget of the Nation. Likewise, 23% will come from the General System of Participations, 13% from the own resources of the territorial entities, 9% from the industrial and commercial companies of the State (nationaland territorial), 4% from the General System of Royalties and 1% as a contribution of international cooperation. At the same time, the Pluriannual Investment Plan of the Development Plan indicates that “in addition, it is estimated that the public investments identified in the Pluriannual Investment Plan will leverage private investments during 2022-2026 to a value of $249.7 trillion by 2022, and it is expected that part of these resources will promote the fulfillment of social objectives together with the national government.”